Reliability of Fine Needle Aspiration Cytology for Salivary Gland Lesions - Gita Rezvani; Farzad Yazdani Bioki; Roya Khatami; Hamed Keramat; Ali Moadabi (Islamic Dental Association of Iran, 2015)
Background and Aim: Fine needle aspiration (FNA) cytology is a safe, reliable, mini-mally invasive and cost-effective technique for the diagnosis of salivary gland lesions. This study aimed to assess the accuracy, reliability and diagnostic value of FNA cytology in Iran. Materials and Methods: A total of 200 records of patients with a history of biopsy or surgical excision of salivary gland lesions along with their histological and cytological examination results were retrieved and evaluated in the Pathology Department of Amir Alam Hospital during 2007-2013. The results of cytological diagnosis were divided into 4 groups of unfavorable, benign, suspicious and malignant. The cytological results were compared with the histological data. The accuracy, sensitivity, specificity, positive predic-tive value (PPV) and negative predictive value (NPV) of FNA cytology were calculated using SPSS version 16.00. Results: Of the specimens chosen for the study, 173 were from the parotid, 22 from the submandibular and 5 from the minor salivary glands. FNA cytological diagnosis was be-nign in 161 cases, suspicious for malignancy in 4 cases, and malignancy in 35 cases. Of 161 cases diagnosed as benign by FNA cytology, 25 were malignant and the frequency of false positive results was 15.5%. The accuracy, sensitivity, specificity, PPV and NPV of the FNA test were 82, 53, 93, 72 and 84%, respectively. Conclusion: A good agreement exists between the FNA results and final histopathological diagnosis of salivary gland tumors. Also, this study showed that FNA cytology has mod-erate accuracy and relative diagnostic value for diagnosis of salivary gland lesions.